A framework for sustainable architecture in Iran with emphasis on the views of scholars - Nemati, M.A.; Bemanian, M.R.; Ansari, M. (Penerbit Universiti Kebangsaan Malaysia, 2017)
Development of the built environment needs to be addressed in a way that is socially and ecologically responsible. There is great urgency to make sustainable interventions in Iran, while built environments are being created without the above engagement. Lack of awareness and consensus on sustainable actions needs formulation of a framework set by scholars analyzing effects of its components in a comprehensive model. The need to develop an instrument for investigation of views of scholars has instigated the researcher to collect the necessary data through interviews and prepare a research questionnaire. Moreover, the exploratory factor analysis survey method was employed, so that structural equation can be used for modeling purposes. The results led to development of a theoretical model to describe views of sustainable architecture in Iran. Results show that environmental and productivity in the use of nature aspects of buildings is the cause of transition to sustainable architecture. Technology, construction and operations of buildings aspects as mediating variables have effects on environmental awareness as dependent variable of transition to sustainable architecture in Iran. The results can pave the path for further research in this area and orient the research priorities for sustainable architecture in Iran.